Analysis of the Role of the Constitution, Legislature, and Judiciary in Maintaining the Principles of Government Effectiveness in Indonesia - Judijanto, Loso; Zainuddin, Zulfa; Bidja, Isnanto (West Science Law and Human Rights, 2024)
This research conducts a thorough document analysis to examine the roles of the Constitution, Legislature, and Judiciary in maintaining government effectiveness in Indonesia. The historical evolution of the Indonesian Constitution is explored, emphasizing its dynamic nature and adaptability to the nation's political and societal changes. The study delves into the separation of powers, constitutional safeguards, and specific provisions influencing government effectiveness. Legislative analysis scrutinizes key acts shaping government operations, emphasizing the role of the legislature in oversight and accountability. Judicial analysis focuses on judicial review, the enforcement of the rule of law, and the judiciary's contributions to legal precedents. Interactions between the three pillars are examined for collaborative synergies and potential challenges. Comparative perspectives and implications for policymakers and legal scholars are discussed, along with recommendations for enhancing government effectiveness. The research identifies future research directions, contributing to a nuanced understanding of the governance landscape in Indonesia.